2008
DOI: 10.1111/j.1460-9568.2008.06069.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of FAK ablation on cerebellar foliation, Bergmann glia positioning and climbing fiber territory on Purkinje cells

Abstract: Focal adhesion kinase (FAK) is a non-receptor tyrosine kinase that is widely expressed in the brain, and plays key roles in various cellular processes in response to both extracellular and intracellular stimuli. Here, we explored the role of FAK in cerebellar development. In the mouse cerebellum, FAK was found to be distributed as tiny cytoplasmic aggregates in various neuronal and glial elements, including Purkinje cells (PCs), Bergmann glia (BG), parallel fiber (PF)-terminals and climbing fiber (CF)-terminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 75 publications
2
18
0
Order By: Relevance
“…Purkinje cells from homozygous conditional knockout mice show a normal phenotype22; (c) kin-32 ( PTK2 ortholog) silencing in C. elegans did not affect viability, development, fertility, locomotion and chemosensory activity.…”
Section: Discussionmentioning
confidence: 94%
“…Purkinje cells from homozygous conditional knockout mice show a normal phenotype22; (c) kin-32 ( PTK2 ortholog) silencing in C. elegans did not affect viability, development, fertility, locomotion and chemosensory activity.…”
Section: Discussionmentioning
confidence: 94%
“…In particular, axons lacking FAK extend more slowly than normal (Rico et al, 2004). To investigate the function of FAK in vivo, we generated pyramidal cell-specific conditional Fak mutants by crossing NEX-Cre mice (Goebbels et al, 2006) (Beggs et al, 2003;Rico et al, 2004;Watanabe et al, 2008), we found that loss of Fak function in pyramidal cells did not alter the gross morphology of the cerebral cortex (data not shown). To test the role of FAK in axonal development, we focused on the hippocampal commissural projection.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular mechanisms that regulate CF synaptogenesis and fine tuning are not well understood. The GluRδ2, which probably acts as an adhesion molecule (41,42), P/Q-type voltage-dependent Ca 2+ channels, insulin-like growth factor (IGF), focal adhesion kinase (FAK), tyrosine-related kinase B (TrkB), myosinVa, glutamate transporter GLAST, a novel brain specific receptor-like protein family BSRP, mGluR1, the α subunit of the Gq subtype of GTP-binding protein, phospholipase Cβ4, and PKCγ were shown to play roles for the development of CF and PC connectivity (42)(43)(44)(45)(46). PKCγ, which has been shown to be activated by Nogo-A (47) was down-regulated in Nogo-A KO and doubled in L7-Nogo-A TG mice, but its role in PC dendritic tree development seems rather complex (23,48) and a possible role of this pathway for the observed effects of Nogo-A remains to be studied in detail.…”
Section: Discussionmentioning
confidence: 99%